Iterative algorithms for split equilibrium problems of monotone operators and fixed point problems of pseudo-contractions. (2nd September 2022) - Yao, Yonghong; Li, Huayu; Postolache, Mihai
Abstract : In this paper, we investigate the split equilibrium problems and fixed point problems in Hilbert spaces. We provide a unified framework for solving such problem in which the involved equilibrium bifunctions f and g are pseudomonotone and monotone, respectively, and the operators S and T are pseudocontractive. We suggest an iterative algorithm for solving the split problem and demonstrate its weak convergence.